2019
DOI: 10.1177/2374373519872088
|View full text |Cite
|
Sign up to set email alerts
|

“I Wish Someone Had Told Me That Could Happen”: A Thematic Analysis of Patients’ Unexpected Experiences With End-Stage Kidney Disease Treatment

Abstract: Background: Preparedness regarding prognosis and treatment options enables patients to cope with uncertainties, make value-based treatment decisions, and set treatment goals. Yet, little is known about the expectedness of end-stage kidney disease (ESKD) patients’ treatment experiences beyond their desire for better treatment education. Objective: To describe unexpected adverse treatment experiences among ESKD patients. Method: The authors conducted 7 focus groups with 55 dialysis patients and living-donor kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
5
9
0
Order By: Relevance
“…In the current study, participants clearly described their immense sense of loss on multiple dimensions. This result consistent with studies conducted in Nigeria [ 18 ], Iran [ 22 ], Francisco [ 23 ], Georgia [ 4 ], and the USA [ 19 ], with those living with CKD, described their lives as being filled with pain and suffering, loss of self, and loss of independence.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the current study, participants clearly described their immense sense of loss on multiple dimensions. This result consistent with studies conducted in Nigeria [ 18 ], Iran [ 22 ], Francisco [ 23 ], Georgia [ 4 ], and the USA [ 19 ], with those living with CKD, described their lives as being filled with pain and suffering, loss of self, and loss of independence.…”
Section: Discussionsupporting
confidence: 90%
“…Self-image, stigma, and suicidal ideations are all considered within the rubric of mental distress by the participants. This complex and far-reaching result was consistent with the studies conducted in India [ 31 ] Nigeria [ 18 ], Iran [ 22 ], Greece [ 32 ], and the USA [ 19 ], where participants described feelings of isolation in the society, physical limitations, and fears of poor clinical results contributing to feelings of sadness, depression, and despair. Further, the lifelong (chronic) dimension of CKD along with the uncertainties with regard to the ability to continue treatments and afford the medications impacted significantly on psychological wellbeing.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… 38 , 39 , 40 However, studies of patients who transition to kidney failure have demonstrated that patients and families believe that people with kidney disease should be informed about these aspects of treatments before developing kidney failure. 41 , 42 Our findings suggest that patient satisfaction may not accurately capture the quality of SDM, and assessments of SDM interventions may benefit from more precise measures, such as the patient-reported measure CollaboRATE. 28 …”
Section: Discussionmentioning
confidence: 90%